Ḥadrāmī scholars in the Malay-Indonesian Diaspora: A Preliminary Study of Sayyid ‘Uthmān - Azyumardi Azra (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 1995)
The absence of in-depth study of the 'ulama Hadhrami archipelago, especially the period after the 18th century when people Hadhrami emigration reached its peak, is something surprising. Indeed, there are records of the 'ulama certain Hadhrami, but many do not provide adequate information. Note that usually only contains a very brief description and not the whole of the presence and role of 'Hadhrami scholars in the history of Islam in the archipelago.It is not surprising, because most of the main motivations arrival Hadhrami people to this part of the world are traded, and not spreading religion. In other words, the arrival of their much more motivated by a desire to improve the economic conditions and acquire wealth. So if some of them are then receive certain positions, such as qadi or imam, is more likely to be motivated by economic interests rather than the interests of religion wages.DOI: 10.15408/sdi.v2i2.833